TEACHERS AND STUDENTS’ PERCEPTION TOWARD CHARACTER EDUCATION IN ENGLISH TEXTBOOKS - PERMANA, DIO RESTA; INDERAWATI, RITA; VIANTY, MACHDALENA (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
This study aimed at investigating how far teachers and students really understand the existence of character education in the curriculum, especially through the teaching and learning process in the classroom by using English textbooks as a medium. There were six teachers and six students who participated in this research. A semi-structured interview with a one-on-one interview was conducted in order to see the perspective of teachers and students about character education in their textbooks. The study revealed that both teachers’ and students’ agreed that character education is essential in creating good individuals with noble characters to tackle moral degradation. Their understanding of character education in the textbooks they were using now was satisfactory. It can be seen through both teachers and students were aware of dealing with character values in the textbooks that embedded in the teaching and learning materials which can be presented both in form of implicit and explicit but they did not know about 18 character values proposed by the government yet.